Women's gymnastics injuries: a 5-year study. - Sands WA; Shultz BB; Newman AP (American Journal of Sports Medicine)
A 5-year prospective study on the time course of women's gymnastics injuries was conducted on a successful NCAA Division I team. Gymnasts recorded injuries on a computer terminal or via computer dot sheets immediately before each training session, including the injured body part, the event or activity, and the date of the injury. The definition of injury was 'any damaged body part that would interfere with training.' Athletes recorded injuries on the 1st day of onset and subsequently until the injury was healed. The initial onset of injury was considered a new injury. Subsequent records of the injury were considered continuing injury. Thirty-seven athletes participated through five collegiate seasons. They accounted for 5602 total training exposures with an average of 151.4 exposures per athlete. The analyses showed that gymnasts trained with an injury approximately 71% of the exposures, and a new injury could be expected from a gymnast during approximately 9% of the exposures. The largest number of injuries were of the repetitive stress syndrome type. The time series information showed that total injuries tended to increase until the middle of the competitive season, while new injuries showed prominent increases during specific training periods and during competition preparation and performance.